Expertise and explicitation in English translations of the Holy Quran - Raoufkazemi, Fatemeh; Khorsand, Majid; Asl, Moussa Pourya; Amirdabbaghian, Amin (Penerbit Universiti Kebangsaan Malaysia, 2020)
With universals of translation budding into an interesting field in translation studies, discussing the nature of translation universals and explicitation as one of the universals of translation emerges as one important strand worthy exploring. In this paper, first of all, the notion of explicitation in translation is introduced, followed by the probable relations between expertise and explicitation discussed in two Arabic-English translations of the Holy Quran. First, a comparison was made between the original text and the translations in terms of explicitation regarding cohesion in context. Second, the translations were compared by studying cohesive markers. In the third step, the study investigated the relationship among features of cohesion, as verified by Halliday and Hassan’s seminal work in this realm, with all instances of explicitation identified on this basis. The fourth stage of the study saw a comparison drawn between the frequencies of explicitation in the translations. The findings pointed to the application of explicitation, somehow affecting the behavior of cohesive markers. Finally, the results of the analysis supported the need for the reasons behind the rate of the relationship between expertise and explicitation in the Arabic-English translations of the Quran. Interestingly, the findings turned out to be in contrast with the hypothesis indicating that the translated texts converted by experienced translators would be more explicit than their original parallel versions. Further, experienced or inexperienced translators transferred most of the ellipsis and substitutions used in the source text in their original form. No clear relationship between the level of expertise of translators and explicitation in translation was discovered. Such detailed investigations of the instances of explicitation in corpora would be attempts to categorize, compare and contrast patterns of occurrence, and provide possible starting points for further similar research.